Spatial interactivity. Sensoriality and design of digital data in the space - Giorgio Dall’Osso; Martina D’Alessandro; Valeria Melappioni (Agathón)
This paper explores the thesis according to which the relationship between urban space, digital data and the user is biunivocal in nature and plays a strategic role in defining a new trajectory of development of the way users inhabit and transform the city. As digital is now invisibly integrated into the activities we perform daily, networks are extending into the real space, demonstrating how technology does not eliminate the human need for physical presence. Architecture must grapple with a non-tectonic reality, and ask itself not how to use the digital to manage data apparatuses to generate dynamic architectural forms, but rather how to turn information into an engine for spaces that can dynamically respond to the needs of the inhabitants.